THE EFFECTIVENESS OF POSTERS ON INCREASING KNOWLEDGE OF THE DANGERS OF SMOKING IN SDIT AL MUDDATSIRIYAH STUDENTS - Rosini, Rosini -; Yulinda, Yulinda (Publication Library and Information Science, 2022)
This study aims to determine the effect of the use of poster media on increasing the knowledge of students of SDIT Al Muddatsiriyah. The study population was fifth-grade students of SDIT Al Muddatsiriyah. This type of research is an experiment using one group pretest-posttest with a sample of 90 respondents. The sampling technique used is saturated sampling. The t test results show the sign value. (2-tailed) equal to 0.000 <0.05, which means t count < from t table. Thus, there is a difference between before and after the treatment on the use of posters, H0 is rejected and H1 is accepted. It is known that the value before being given health literacy is equal to 32.56 and after being given treatment, the knowledge of students towards the dangers of cigarettes increases as much as 38.26. It can be said concluded that the media poster can increase students' knowledge about the dangers of smoking.Â